Scribal culture and intertextuality: literary and historical relationships between Job and Deutero-Isaiah - Kwon, JiSeong James (Forschungen zum Alten Testament / 2, 2016)
JiSeong James Kwon discusses similar linguistic expressions and themes between Job and Deutero-Isaiah, and attempts to find out a common historical background. He argues that both Job and Deutero-Isaiah significantly reflect common scribal ideas, although each text belongs to wisdom and prophetic genre. - From the back of the book